FINANCIAL MANAGEMENT AND FINANCIAL REPORTING TRAINING FOR SMALL BUSINESSES IN NEGERI KEDAH - Hamdi Agustin; Halimahtussakdiah Halimahtussakdiah; Haswari Hasan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The problems faced by small business actors in Kedah Malaysia are: 1. The lack of knowledge of business actors regarding business financial management, such as business and household finances are still mixed up. 2. Bookkeeping is still kept simple in their efforts. The problem that often occurs in small businesses is that household finances often get mixed up with business finances. The same thing happened with businesses in Kedah, Malaysia. This problem raises the problem of not being able to determine the results of operations precisely. This may occur due to a lack of knowledge or understanding of business actors regarding the recording of their business finances or they may consider this financial separation to be less important. The solution that can be done is training to make bookkeeping so that they can accurately calculate and know the profit or loss of their business results. With this financial report, it will be possible to carry out Financial Management and Financial Reporting to manage small business finances in Kedah Malaysia. The target of this Community Service program is: business actors in Kedah Malaysia are able to do bookkeeping properly and have the skills to record financial items correctly. The output produced in this activity is the ability of business actors to properly record, book and report finances in order to obtain maximum profit from operations. Seeing the resulting output, it is hoped that business actors in Kedah Malaysia will be able to develop their business more.